Management of Teacher Discipline Development Through a Web-Based QR Code Attendance System with WhatsApp E-Notifications at SMK (Vocational School) Nahdlatul Ulama (NU) Kaplongan Indramayu - Ade Apriyanto; Muhammad Sholeh; Wawan Setiawardani (MASI Mandiri Edukasi, 2025)
Teacher attendance recording in SMK NU Kaplongan was still manual before using the digital attendance system for years ago. More than half of the teachers did not fill out the attendance list, creating a potential for fraud and negatively impacting learning. This study aims to analyse how teacher discipline development is managed through a web-based QR code attendance system with WhatsApp e-notifications at SMK NU Kaplongan Indramayu, and to evaluate the impact of this management on teacher discipline development through the attendance system technology. This study uses a qualitative method with an exploratory case study approach. Primary data sources for this study include 1 person—the school principal, 1 person—the curriculum manager, 1 person—the head of IT, and 5 people—teachers. The selection of informants is not random but is based on purposive criteria and specific considerations. Data collection was conducted from December 2024 to January 2025. The data collection techniques used in this study are observation, interviews, documentation, and a combination of these methods. Data analysis techniques involve categorising data, breaking it down into units, synthesising it, organising it into patterns, selecting it for discussion, and finally drawing conclusions. The results of the study show that the development of teacher attendance discipline through a web-based QR code attendance system with WhatsApp e-notifications is managed effectively, including planning, organising, implementing, and supervising. However, the impact of this system on teachers' disciplinary awareness of barcode card use at arrival and departure remains low, with arrival at 53-63% and departure at 11-13%. Monitoring teacher attendance through this system does not guarantee that teachers consistently utilise a web-based QR code attendance system with WhatsApp e-notifications.